2002
DOI: 10.1108/00438020210424244
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial implications of shift work: a case study

Abstract: Explores possible effects of work related problems and fatigue on shift workers' attitude, aptitude and job satisfaction. Uses a simple case study to explore views identified from a literature review. Data were collected from subjective responses using questionnaires among adult male subjects working on a weekly rotating threeshift system in a shoe factory in Dhaka, Bangladesh. Results indicate that this particular form of shift work is seen as disruptive to family, conjugal and social life; it curtails leisur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…In the current study, the high level of stress was shown not necessarily related to presence of psychosis among the security guards. Nevertheless, the findings confirmed that stress may induce mental health problems among security guards, as suggested by previous studies [20] [24][25] [30]. Therefore, stress can be established as a risk factor for mental health problems among security guard.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In the current study, the high level of stress was shown not necessarily related to presence of psychosis among the security guards. Nevertheless, the findings confirmed that stress may induce mental health problems among security guards, as suggested by previous studies [20] [24][25] [30]. Therefore, stress can be established as a risk factor for mental health problems among security guard.…”
Section: Discussionsupporting
confidence: 70%
“…It was found that there is significant relationship between stress and various dimensions of with Aggressiveness: A Study on Security Guards mental health, which may lead to severe mental health problems such as PTSD, and eventually may lead to violence and aggression [27][28]. The needs of the job itself require a significant higher level of stress, as proved in a study where security guard had the highest percentage (65.7%) of extensive job stress of all professions [29], and it has been proved to induce negative mental health and mood instability [20] [24][25] [30]. Therefore, association between stress and mental health problems can be hypothesized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Scale of the negative effects of worktime is an adapted translation of the original scale by Ahasan et al (37). It covers effects of worktime on family life, social life, and health, with questions such as "My worktime disturbs my family life" or "My worktime restricts my social life".…”
Section: Questionnaires and Response Evaluationmentioning
confidence: 99%
“…It is gaining in importance as the prevalence of non-traditional work arrangements such as flexitime, telework, and irregular shift-work increases. Research largely substantiates the idea that a worker' s social and family life, and the range and frequency of participation in leisure activities are adversely affected by atypical work schedules (Ahasan, Mohiuddin, & Khaleque, 2002;Herbert, 1983;Pocock, van Wanrooy, Strazzari, & Bridge, 2001). Mothers have experienced these problems to a greater extent than fathers because of the gendered nature of domestic responsibilities and the additional time many women spend on housework and child care (Barnes, Bryson, & Smith, 2006;Fast & Frederick, 2004;La Valle, Arthur, Millward, Scott, & Clayden, 2002).…”
Section: Traditional Perspectives and New Issuesmentioning
confidence: 97%